Planting an Indigenous Church : The Case of the Borneo Evangelical Mission - Tan, Jin Huat (Book collections on Project MUSE., 2011)
The story of the Borneo Evangelical Mission (BEM) and the Sidang Injil Borneo (SIB) highlights the importance of intentinal mission policy and its sustained implementation for the development of an indigenous church. Having a clearly defined exit policy provided the necessary impetus for the BEM to plant a church that was able to stand on its own feet. A number of contextual factors, such as the administrative policies of the Brooke government and the changing political situations in Sarawak and Malaysia, have threatened to limit the growth of BEM and SIB. However, the abilities of indigenous leaders to take ownership of the SIB have enabled them to navigate these challenges in a manner that has made it the most significant indigenous church in Malaysia.